If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y = (4y + 18) Reorder the terms: 6y = (18 + 4y) Remove parenthesis around (18 + 4y) 6y = 18 + 4y Solving 6y = 18 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. 6y + -4y = 18 + 4y + -4y Combine like terms: 6y + -4y = 2y 2y = 18 + 4y + -4y Combine like terms: 4y + -4y = 0 2y = 18 + 0 2y = 18 Divide each side by '2'. y = 9 Simplifying y = 9
| 7-5(x+2)=3(x+2) | | F(x)=x+1 | | 12(4+6)-(8-7)=0 | | -3(3x+10)=4(x+2) | | 2/3x=24-10 | | 0=x+7x+12 | | (30-x)+3= | | -3(3x+10)=4(c+2) | | x*0.03=460 | | 7(7-3x)=x-11 | | 3x=112+6x-40 | | s^2-10s-96= | | 3(x-1)-4(x+3)=5 | | 0.7(6x+3)=1.1-(x+5) | | 9=yz | | 6x-22=2x+34 | | 0.7(3x+3)=1.1-(x+2) | | 4(8-5x)=2x-4 | | 2/3x-5/6=10 | | X/3-4=-6 | | (t-10)(t+11)= | | p=s/14 | | x^3-20x^2+64x=0 | | 8/9z-1/2=-2/3z+1/6 | | 300+2x-125-7x=75 | | 1/3(1/2-1/3)-1/3(1/3-1/2) | | u-v=18 | | 3/5x+5=14 | | 2n^2-2n=7 | | 3-(x+1)=2-(x+6) | | w-6=8 | | 3(-4x-4)-5=16 |